Relating design principles with Islamic spirituality based on the transformation of nature in design process - Muslim, Zulkifli (Universiti Putra Malaysia Press, 2018)
The biological, physical and visual aspects of the environment influence life philosophy, culture, society, tradition and creativity development. However, the potential of environmental resources such as plants can contribute to the design production has not been examined adequately and analyzed systematically. There is a lack of exploration on linking the design process and idea with the Islamic principles embedded in the Islamic spirituality. This paper presents an analysis of the design process of nature (plants) and its relationship with the Islamic principles, design and qualities. The principles and terminology are discussed in relation the Islamic spirituality and the qualities of Asma’ ul Husna to gain a comprehensive understanding of the creative process and the aesthetic content of design products. The study highlights the potential to interpret design works based on the internal process of human creativity. The link to the spiritual values originated from the Light of the Creator, Allah swt has been made evident in the creative process. The findings provide a process of linking the external and internal processes of designing exemplified by an analysis of nature as the source of ideas thus increases the value and content of Islamic design products.